Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Sekolah - Fitria Khairunnisa Anwar; Ela Ela; Putri Ananda; Yessy Rifmasari (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The porpuse of this discussion is to find out and analyze the leadership of elementary school principals to improve school quality. The method used is a literature review. The data collection technique is by reviewing or exploring several books, journals, and other documents tat are considered relevant. This research discusses the description of leadership and the leadership stile style of school principals. The principals leadership is a determinant of the success of realizing educational goals in the school which have been outlined in the school’s vision and mission. Leadership style is the way a leader behaves, communicates, and interacts with other people in influencing people to do something. Several leadership styles that can be implemented by school principals: namely managerial leadership, transformational leadership, transactional leadership, teaching leadership, and positive leadership. School principals must carry out their duties professionally in order to achive national education goals.